Tropical–Mid-Latitude Interactions: Case Study of an Inland-Penetrating Atmospheric River During a Major Winter Storm Over North America. Issue 3 (27th May 2019) - Mo, Ruping; Lin, Hai
ABSTRACT: A detailed analysis is performed on an inland-penetrating atmospheric river (AR) driven by and coupled to a Colorado cyclone in the first week of February 2016. This winter weather system was initiated by a trough of low pressure moving across the Rocky Mountains from the California coast. The low-level jet ahead of the trough was capable of extracting water vapour from the Gulf of Mexico to feed a cyclone on the lee side of the Rocky Mountaains, and the jet stream eventually transformed into a powerful AR. The warm, moist flow from the south produced a narrow band of heavy precipitation along the major axis of the AR across the central and eastern United States and generated significant freezing rain in parts of the northeastern United States and eastern Canada as the AR flowed over the warm front. It is suggested that, in an operational weather forecasting and warning environment, ARs can be easily identified by using the vertically integrated horizontal water vapour transport, and the major AR contribution to heavy precipitation can be estimated from the horizontal moisture convergence. It is demonstrated that the AR analysis in this case can assist operational meteorologists in understanding and conceptualizing winter storm development and the associated high-impact weather pattern. The operational predictability of this winter storm and its possible teleconnection with the Madden–Julian Oscillation (MJO) are also investigated. Our lagged composite analysis reveals that a statistically significant increase in water vapour transport from the Gulf of Mexico over the North American continent could occur about 10–20 days after the MJO-related convection anomaly reaches the tropical Indian Ocean.